Modulation of TRIB3 and Macrophage Phenotype to Attenuate Insulin Resistance After Downhill Running in Mice - Luo, Wei; Zhou, Yue; Tang, Qiang; Ai, Lei; Zhang, Yuan (Frontiers in Physiology, 2021)
Eccentric exercise training accompanied by a low-fat diet can prevent insulin resistance (IR) and is currently an effective method for treatment of IR induced by high-fat diet (HFD) associated obesity. However, the molecular mechanisms underlying this improvement of IR in adipose tissue are still not completely clear. In this study, 5-6-week-old male mice were randomly divided into standard control diet (SCD) group (SC, n=12) and HFD group (HF, n=72). After 12 weeks, 12 mice in each group were randomly sacrificed. The remaining mice in HF group were randomly submitted to one of the following experimental protocols for 8 weeks: Obesity-HFD-sedentary (OHF-Sed, n=14), Obesity-HFD-exercise (OHF-Ex, n=16), Obesity-SCD-sedentary (OSC-Sed, n=14), and Obesity-SCD-exercise (OSC-Ex, n=16). All obese mice in exercise group were subjected to downhill running. Half of mice in each group received insulin injection (0.75 U/kg) before sample collection. Epididymal fat was removed and weighed. Adipocyte size and inflammatory cell infiltration were observed by H&E staining. Both basal and insulin-stimulated GLUT4 fluorescence and protein contents were detected by Immunofluorescence and Western blot. Levels of IL-1β and IL-10 were detected by ELISA. Protein contents of iNOS, Arg-1, TRIB3, p-AKT, and AKT were determined by Western blot. CD86 and CD206 fluorescence were determined by Immunofluorescence. The results showed that HFD fed for 12 weeks induced IR accompanied by adipose tissue macrophages M1 polarization (increased iNOS protein content and CD86 fluorescence) and TRIB3-AKT activation. Downhill running accompanied by a low-fat diet attenuated IR (p<0.01), reduced inflammation levels (increased IL-10 protein content and decreased IL-1β protein content), inhibited adipose tissue macrophages M1 polarization (decreased iNOS protein content and CD86 fluorescence) and promoted M2 polarization (increased Arg-1 protein content and CD206 fluorescence), and suppressed TRIB3-AKT signaling. We concluded that downhill running accompanied by dietary fat regulation attenuates HFD-related IR in mice, which may be associated with reduced TRIB3-AKT signaling and activated M2 macrophages.